Student-centered Pedagogy and Real-world Research: Using Documents as Sources of Data in Teaching Social Science Skills and Methods. (January 2018) - Peyrefitte, Magali; Lazar, Gillian
This teaching note describes the design and implementation of an activity in a 90-minute teaching session that was developed to introduce a diverse cohort of first-year criminology and sociology students to the use of documents as sources of data. This approach was contextualized in real-world research through scaffolded, student-centered tasks focused on archival material and contemporary estate agents' brochures so as to investigate changes in the suburbs that surround a university in north London. To contribute to the growing discussion on pedagogic dialogical spaces in teaching research methods, we provide empirical evidence of students' greater engagement via group work and the opportunity to draw on experiential knowledge in analyzing sources. Beyond stimulating students' engagement with research skills and methods, the data also show the value of our approach in helping students develop their analytical skills, particularly through a process of comparison and contrast.